Synergistic Interaction Between Heme Oxygenase (HO) and Nuclear-Factor E2- Related Factor-2 (Nrf2) against Oxidative Stress in Cardiovascular Related Diseases - Fomusi Ndisang, Joseph (Current Pharmaceutical Design, 2017)
Background: Nuclear factor-erythroid related factor-2 (Nrf2) is a master regulator of transcriptional activation of anti-oxidants in cells. Similarly, heme oxygenase (HO) is a cytoprotective protein with anti-oxidant effects. This review article will shed more light on the interaction between Nrf2 and HO. Methods and Results: A PubMed search was done for recent articles on Nrf2 and HO. These studies suggested that under normal physiological conditions, Nrf2 is bound within the cytoplasm to its repressor, Kelch-like ECHassociated protein (Keap1), an oxidative stress sensor. Upon activation, Nrf2 translocates to the nucleus and binds to the antioxidant-response-element located at the promoter region of some anti-oxidants including the cytoprotective protein HO. Since the HO-1 gene harbors binding site for Nrf2, mutual stimulatory and regulatory effects between Nrf2 and HO-1 have been reported. Accordingly, the interaction between Nrf2 and HO-1 has been implicated in the regulation of many physiological anti-oxidants including superoxide dismutases, catalase, glutathione S-transferase, peroxidase, NAD(P)H quinone oxidoreductase, and thioredoxin. Conclusion: Although an overwhelming body of evidence has underscored unique anti-oxidant attributes of HO- 1 and Nrf2, emerging evidence suggests that the cytoprotective activities of Nrf2 and HO-1 may be attributed, at least in part, to the potentiation of different anti-oxidants in physiological mileu. Since Nrf2 binds to the antioxidant responsive element of HO-1, the coordinated regulation of Nrf2 and keap1 by the HO-system may constitute the basis of many physiological effects of HO-1 including its effects against oxidative stress and inflammation in a wide spectrum of cardiovascular, cardio-metabolic and other related diseases.
Keywords: inflammation